Determinants of Corporate Performance (CP) in Public Health Service Organizations (PHSO) in Eastern Province of Sri Lanka: A Use of Balanced Score Card (BSC) - Ismail, M.B.M.; Velnampy, T.; Dean (My University, 2013)
Corporate performance in public health service organizations is how public health service organization looks at its patients, key disease treatment service lines, learning & growth and resources. Therefore, many authors have used BSC for organisational performance. This study tries to determine factors affecting performance of PHSOs; know the reliability and validity of items & factors and to create a mathematical equation model. Data are collected in both secondary and primary sources. Researcher collected 54 from corporate performance in public health service organisations’ performance during the period of 2012 to 1996. Primary data have been collected using questionnaire. Since this is a pilot study researcher selected only 100 hospital employees out of 3 selected government hospitals in Addalaichenai Divisional Secretariat of Ampara District. Collected questionnaires have been analysed by a factor analysis and regression analysis. Results found that patient, key service line, learning & growth and resource factors have been identified as performance of public health service organizations. Cronbach alpha for items in these factors are 0.888, 0.807, 0.651 and 0.857. It shows high reliability for items. KMO is used to know the statistical validity of factors. In this study, values of KMO for patient, key service line, learning & growth and resource are 0.687, 0.502, 0.559 and 0.818. Content validity and convergent validity are higher. Discriminant validity are lower statistically. Log log model is the best fitted model than linear models.
Keywords: Corporate performance; Public Health Service Organizations; Eastern Province; Sri Lanka; Balanced Score Card (BSC)